Search for Higgs boson production in association with a high-energy photon via vector-boson fusion with decay into bottom quark pairs at p s = 13 TeV with the ATLAS detector - Fiolhais, M. C. N. (2021)
A search is presented for the production of the Standard Model Higgs boson in association with a high-energy photon. With a focus on the vector-boson fusion process and the dominant Higgs boson decay into b-quark pairs, the search bene ts from a large reduction of multijet background compared to more inclusive searches. Results are reported from the analysis of 132 fb1 of pp collision data at p s = 13TeV collected with the ATLAS detector at the LHC. The measured Higgs boson signal yield in this nal-state signature is 1:3 1:0 times the Standard Model prediction. The observed signi cance of the Higgs boson signal above the background is 1:3 standard deviations, compared to an expected signi cance of 1:0 standard deviations.